2003
DOI: 10.1523/jneurosci.23-02-00416.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Second Galanin Receptor GalR2 Plays a Key Role in Neurite Outgrowth from Adult Sensory Neurons

Abstract: Expression of the neuropeptide galanin is markedly upregulated within the adult dorsal root ganglion (DRG) after peripheral nerve injury. We demonstrated previously that the rate of peripheral nerve regeneration is reduced in galanin knock-out mice, with similar deficits observed in neurite outgrowth from cultured mutant DRG neurons. Here, we show that the addition of galanin peptide significantly enhanced neurite outgrowth from wild-type sensory neurons and fully rescued the observed deficits in mutant cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
104
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 48 publications
8
104
0
1
Order By: Relevance
“…Decreased orexin and melanin-concentrating hormone in the perifornical lateral hypothalamus (Karatayev et al, 2010) Increase in opiate withdrawal behavior (Zachariou et al, 2003) Decreased sensitivity to nicotine and no increase in ERK2 activation in mice that showed nicotine conditioned place preference (increase in WT) (Neugebauer et al, 2011) Increase in secreting sweat glands following thermal stimulation (Vilches et al, 2012) GAL 1 (Jacoby et al, 2002)/C57BL/6J and 129T2/SvEmsJ Increased sensitivity to both heat and cold intact. Increased duration of pain-like behavior after nerve injury (Blakeman et al, 2003) No difference in mechanical or thermal thresholds in intact animals but increased hyperalgesia after thermal injury and faster recovery after spinal nerve ligation (Malkmus et al, 2005) No difference in regeneration in vivo (Blakeman et al, 2003) or in vivo (Blakeman et al, 2003;Mahoney et al, 2003a) Increase in opiate withdrawal behavior Spontaneous seizures and reduced plasma levels of IGF-1. No sex difference but strain difference in seizures; not present in mice on 129/Sv background (Jacoby et al, 2002) Impaired response to trace cued fear conditioning (Wrenn et al, 2004) Mild glucose intolerance after feeding and impaired glucose elimination.…”
Section: Galanin Genes and Peptides-genomicmentioning
confidence: 99%
“…Decreased orexin and melanin-concentrating hormone in the perifornical lateral hypothalamus (Karatayev et al, 2010) Increase in opiate withdrawal behavior (Zachariou et al, 2003) Decreased sensitivity to nicotine and no increase in ERK2 activation in mice that showed nicotine conditioned place preference (increase in WT) (Neugebauer et al, 2011) Increase in secreting sweat glands following thermal stimulation (Vilches et al, 2012) GAL 1 (Jacoby et al, 2002)/C57BL/6J and 129T2/SvEmsJ Increased sensitivity to both heat and cold intact. Increased duration of pain-like behavior after nerve injury (Blakeman et al, 2003) No difference in mechanical or thermal thresholds in intact animals but increased hyperalgesia after thermal injury and faster recovery after spinal nerve ligation (Malkmus et al, 2005) No difference in regeneration in vivo (Blakeman et al, 2003) or in vivo (Blakeman et al, 2003;Mahoney et al, 2003a) Increase in opiate withdrawal behavior Spontaneous seizures and reduced plasma levels of IGF-1. No sex difference but strain difference in seizures; not present in mice on 129/Sv background (Jacoby et al, 2002) Impaired response to trace cued fear conditioning (Wrenn et al, 2004) Mild glucose intolerance after feeding and impaired glucose elimination.…”
Section: Galanin Genes and Peptides-genomicmentioning
confidence: 99%
“…GALR2 has been implicated in the mediation of galanin's effect on jejunal contraction (54), stimulation of growth hormone and prolactin secretion (11,40), myometrial contraction (38), seizure susceptibility (34), peripheral nerve regeneration (8,32), hippocampal neuroprotection (12,33), and the response to axotomy in motor and sensory neurons (48,58). In the case of GALR2, its mRNA has been localized to hypothalamic nuclei, hippocampus, amygdala, several regions of the cortex, and the dorsal root ganglion (reviewed in references 11, 20, 29, and 39) and has been shown to be regulated following peripheral nerve axotomy (48,58).…”
mentioning
confidence: 99%
“…Furthermore, GALR2 has been shown to stimulate mitogen-activated protein kinase via G omediated signaling (21). A more recent study reported that GALR2 plays a key role in neurite outgrowth from adult sensory neurons via a PKC-dependent pathway (22). However, so far very little information has been available on the membrane distribution of the GALRs and their intracellular trafficking.…”
mentioning
confidence: 99%